Do Grow-Your-Own Programs Work? Evidence from the Teacher Academy of Maryland - David Blazar; Wenjing Gao; Seth Gershenson; Ramon Goings; Francisco Lagos (Institute of Labor Economics (IZA), 2024)
Local teacher recruitment through "grow-your-own" programs is a prominent strategy to address workforce shortages and ensure that incoming teachers resemble, understand, and have strong connections to their communities. We exploit the staggered rollout of the Teacher Academy of Maryland career and technical education certificate program across public high schools, finding that exposed students were more likely to become teachers by 0.6 percentage points (pp), or 47%. Effects are concentrated among White girls (1.4pp/39%) and Black girls (0.7pp/80%). We also identify positive impacts on wages (5% on average/18% for Black girls), countering a prevailing narrative that teaching leaves one worse off financially relative to other labor market opportunities.
Keywords: I20; J24; H52; 330; earnings; occupational choice; college major choice; high school curricula; teaching